Dynamics resource allocation via virtual machine for cloud computing / Mohd Badrulhisham Ismail - Ismail, Mohd Badrulhisham (2014)
Latest trend in green computing and cloud computing require efficiency in consolidating virtual machine without degrading quality of service. This study, focus on minimizing the migration of Virtual Machine to produce lowest power consumption. To achieve this objective, a new algorithm is used to calculate the fly on the Lower and Upper Threshold Limit using Statistical Process Control theory. This new algorithm is called Dynamics Threshold Optimize System. Three sigma theories are applied in order to get the desire range for the threshold limit. This study applies Optimize Warm Threshold Limit as a secondary diffriihm to optimize the Lower Threshold Limit. This technique is used to determine the mod value from a range of mean value and existing Lower Threshold Limit. If the mod value is higher than the existing Lower Threshold Limit then it will replace the existing Lower Threshold Limit.